Biomass derived interconnected hierarchical micro-meso-macro- porous carbon with ultrahigh capacitance for supercapacitors. (June 2019) - Yang, Song; Wang, Shulan; Liu, Xuan; Li, Li
Abstract: The cost-effective biomass derived carbon with high electrochemical performance is highly desirable for the sustainable development of advanced energy storage devices. However, most of the reported biomass carbon materials suffer from the low capacitance in the range of 0–400 F/g as the electrode for supercapacitor. Herein, we reported, for the first time, the fabrication of tri-modal porous carbon with a record high capacitance of 550 F/g at 0.2 A/g for biochar materials from shaddock endotheliums by a feasible method combined with metal ion impregnation and molten KOH activation. The as-prepared carbon also showed an outstanding energy density of 46.88 Wh/kg with a power density of 300 W/kg in 1 M BMIMBF4 /AN with high capacitance retention over 93.7% after 10000 cycles, which is rarely achieved by the peer reported biochars. Its high electrochemical performance is attributed to combined contributions from high surface area (1265 m 2 /g), hierarchical porous structure, high graphitization level and abundant heteroatoms (about 10 atom%) co-doping. The work provides an outstanding renewable candidate and a feasible route design strategy for fabrication of high performance electrode materials. Graphical abstract: Image 1